Uveitis in childhood-onset systemic lupus erythematosus patients: a multicenter survey - Kahwage, Paola Pinheiro; Ferriani, Mariana Paes Leme; Furtado, João M.; de Carvalho, Luciana Martins; Pileggi, Gecilmara Salviato; Gomes, Francisco Hugo Rodrigues; Terreri, Maria Teresa; Magalhães, Claudia Saad [UNESP]; Pereira, Rosa Maria Rodrigues; Sacchetti, Silvana Brasilia; Marini, Roberto; Bonfá, Eloisa; et al. (Springer Nature, 2017)
The aim of this study is to assess uveitis prevalence in a large cohort of childhood-onset systemic lupus erythematosus (cSLE) patients. A retrospective multicenter cohort study including 852 cSLE patients was performed in ten pediatric rheumatology centers (Brazilian cSLE group). An investigator meeting was held and all participants received database training. Uveitis was diagnosed through clinical assessment by the uveitis expert ophthalmologist of each center. Patients with and without uveitis were assessed for lupus clinical/laboratory features and treatments. Uveitis was observed in 7/852 cSLE patients (0.8%). Two of them had ocular complications: cataract and irreversible blindness in one patient and retinal ischemia with subsequent neovascularization and unilateral blindness in another. Uveitis was identified within the first 6 months of cSLE diagnosis in 6/7 patients (86%). Comparison of a subgroup of cSLE patients with (n = 7) and without uveitis (n = 73) and similar length of disease duration showed that patients with uveitis had increased SLEDAI-2K score (19 vs. 6; p < 0.01). In addition, fever (71 vs. 12%; p < 0.01), lymphadenopathy (29 vs. 1.4%; p = 0.02), arthritis (43 vs. 7%; p = 0.02), and use of intravenous methylprednisolone (71 vs. 22%; p = 0.01) were higher in cSLE patients with uveitis, as compared to those without this manifestation, respectively. Presence of fever was significantly associated with uveitis, independently of SLEDAI scores or use of intravenous methylprednisolone pulses, as shown by adjusted regression analysis (adjusted prevalence ratio 35.7, 95% CI 2.4–519.6; p < 0.01). Uveitis was a rare and initial manifestation of active cSLE patients. Early recognition is essential due to the possibility of irreversible blindness.
Keywords: Childhood-onset systemic lupus erythematosus; Cohort study; SLEDAI; Uveitis